Effects of intimate partner violence against women in international micro and small enterprises relationships: The mediator role of capabilities - Ponce-Gómez, Jazmín E.; Vara-Horna, Arístides; Valenciano-Mañé, Alba; Dornberger, Utz (Frontiers in Psychology, 2022)
While previous studies have explored multiple constraints affecting women exporters, the effects of intimate partner violence against women (IPVAW) are still unexplored in the literature. Thus, this study aims to probe first whether women owners of micro and small enterprises (MSEs) in export markets experience IPVAW. Secondly, it aims to explore the effect of IPVAW on their relationship quality with business partners, mediated by the performance of export capabilities. Using a structured questionnaire applied through personal interviews, we surveyed 57 female owners of exporting MSEs in Peru. Partial least squares structural equation modeling was used to analyze the data and test the model. The preliminary findings indicate that women exporters who experience IPVAW are more likely to face problems performing export capabilities. In turn, these performance problems seem to affect the quality of their relationships with importers and suppliers. Moreover, there is a direct relationship between IPVAW and problems in performing export capabilities and between issues performing capabilities and the relationship quality. Our theoretical contribution is a conceptual model that proposes the variable "Problems Performing Capabilities" as a mediator to measure the effects of IPVAW on exporting MSEs owned by women. Our findings urge policymakers and trade organizations boosting women-owned export enterprises to include initiatives that address and prevent IPVAW in their export promotion programs.